(untitled) (Global Journal of Science Frontier Research, 2018)
The beginning to electrodynamics assumed such amperes, Faraday, Veber, Maxwell. These scientists on the primitive research established those laws, which we use to the these examine in the dark of prejudices and superstition the top of t electrodynamics is. But those electrodynamics and today, they speak, that not all problems equations is not contained the information about pow systems, but the Lorentz force, which defines such an experimental postulate. Therefore electrodynamics itself consists as of two not together parts. From one side this wave equation for the electromagnetic waves, while another which makes it possible to calculate power field is also introduced not on the basis experimental facts and does